180k views
0 votes
G(x)=-2x-3 f(x)=[x+1]-4 can you determine the solution to the system of equations-explain how you got it thanks

1 Answer

3 votes

Answer:

(0,-3)

Explanation:

To find the system you can use either elimination or substitution. First convert G(x) and f(x) into the variable y, it will make it easier to solve.

y = -2x-3

y = [x+1]-4 Simplify this equation

y = -2x-3

y = x-3 Next, substitute y in the first equation for the y in the second equation to solve for x.

-2x-3=x-3 Solve for x.

-3x=0

x=0, now solve for y by plugging in the x value into either equation.

y=-2(0)-3

y=-3, This means that the solution to the system is (0,-3).

User James Kuang
by
5.3k points